2010
DOI: 10.1111/j.1365-2427.2010.02416.x
|View full text |Cite
|
Sign up to set email alerts
|

Subtle top‐down control of a freshwater meiofaunal assemblage by juvenile fish

Abstract: 1. Top-down control of prey assemblages by fish predators has been clearly demonstrated in lakes (for zooplankton prey) and rivers (for macroinvertebrate prey). Fish predation can have a significant impact on the body size of prey assemblages; often large-bodied prey are reduced in abundance, and indirect facilitation of small-bodied prey occurs potentially initiating a trophic cascade. 2. Benthic communities in aquatic ecosystems also include a numerous and functionally important meiofaunal-sized component, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 65 publications
(111 reference statements)
2
15
0
1
Order By: Relevance
“…This may have been the result of indirect facilitation by fish predation. A similar increase in small‐sized prey following fish predation (or, conversely, a reduction when fish predators were excluded) has been demonstrated in small‐scale freshwater experiments (Dineen & Robertson, ; Weber & Traunspurger, ). For bottom‐feeding fish (e.g.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…This may have been the result of indirect facilitation by fish predation. A similar increase in small‐sized prey following fish predation (or, conversely, a reduction when fish predators were excluded) has been demonstrated in small‐scale freshwater experiments (Dineen & Robertson, ; Weber & Traunspurger, ). For bottom‐feeding fish (e.g.…”
Section: Discussionsupporting
confidence: 66%
“…Many fish species, including juvenile carp, are known to be size‐selective predators, such that predation may change not only abundance and biomass but also the body size distribution of meiofaunal prey populations (Dineen & Robertson, ; Weber & Traunspurger, ,b), as demonstrated for fish predation of zooplankton (e.g. Brooks & Dodson, ; Sih et al ., ) and macroinvertebrates (Meissner & Muotka, ).…”
Section: Discussionmentioning
confidence: 99%
“…In con trast to these results, nematode abundances were not sig nificantly reduced by the two epibenthic feeders examined in this study, the roach and the ninespine stickleback, both of which pick up food-source organisms from the sedi ment (Kottelat & Freyhof, 2007). Many fish species are size-selective predators (Dineen & Robertson, 2010), as observed in this study for some of the fish species and juvenile stages with respect to their nematode prey. By contrast, juvenile stages of C. carpio (scaled) and C. carpio (mirror) fed very effectively on all size classes of nematodes, as did G. gobio, although with increasing body size it no longer consumed nematodes < 0.5 mm (Fig.…”
Section: Discussionsupporting
confidence: 64%
“…As primary consumers, meiofauna influence lake ecosystem processes by reducing microfauna (Perlmutter, and Meyer 1991;Borchardt, and Bott 1995) and by stimulating microbial activity through moderate grazing, bioturbation, and excretion (Traunspurger et al 1997;Hakenkamp et al 2002;Mathieu et al 2007). Meiofaunal organisms are not only closely linked to the lowermost trophic level, but also constitute an important food source for larger vertebrates and invertebrates (Schmid, and Schmid-Araya 2002;Dineen, and Robertson 2010;Spieth et al 2011). However, nearly all studies of freshwater meiofauna published so far have dealt with sediment-associated meiofauna whereas general information on meiofauna in the periphyton of lakes is scarce, with only a few studies reported to date (e.g., Meschkat 1934).…”
Section: Introductionmentioning
confidence: 99%